Interfacial behavior of natural and model asphaltenes : a multi-scale approach (2020)
Asphaltenes have a predominant role in the interfacial behavior of crude oil. Fluid-fluid interfaces are ubiquitous in recovery, treatment, and transport processes for the crude oil industry having a determinant influence on their performance. Understanding different interfacial phenomena when asphaltenes are present is a critical challenge for efficiency and environmentally safe operations. This understanding represents a modern engineering challenge due to their complex molecular nature, the wide variety of chemical motifs, and dynamic functionalities. An alternative to address this complex challenge is the use of rationally designed molecules that serve as asphaltene model compounds reproducing the main features in terms of sorption and interfacial dynamics. The use of asphaltene model compounds, whose molecular characteristics are known, generates a solid framework to connect defined molecular structural characteristics with their interfacial properties. This approximation provides relevant insights to the comprehension of the interfacial activity of asphaltenes. Shedding light on such a complex system requires building a comprehensive view of the phenomena. Through the multi-scale approach presented here, isotropic and anisotropic interfacial deformations and dynamic structural visualization are coupled to construct connections at the molecular, microscopic, and millimetric scales to draw fundamental structure-properties relationships for natural and model asphaltenes at the decane-water and air-water interfaces.